Traffic Impact Analysis of Tajur Bogor Mall Boxies Building on Roads - Maulana, Asep; Rulhendri, Rulhendri; Chayati, Nurul (Universitas Ibn Khaldun Bogor, 2023)
Traffic congestion that occurs almost evenly throughout the Bogor City area can be caused by several main factors, namely. The narrower roads and the increasing number of motorized vehicles result in congestion. The area of Bogor City, which is only 11,850 ha with a road length of 783,412 km, is already congested to accommodate the number of vehicles that are increasingly exceeding the carrying capacity of the road. In addition, the rapid development of business and trade areas in the city of Bogor spurred changes in traffic intensity. This study aims to create a model of generation and attraction caused by land use such as Educational Buildings, Industrial Estates, Traditional Markets and Supermarkets located in the sub-district. Research data retrieval is carried out using primary and secondary data methods, then the data is processed using (Trip Generation Manual) then modeled with (Software Saturn). The number of generation and towing in the studied area is 491 trips/hour. With Service Levels ranging from C to F. Then the design equation for transportation modeling for the East Bogor sub-district in 2021 is Y = 2963.66+0.840(X) then in 2026, namely Y = 2963.66+0.840(X).